International Organizations are Here to Stay - J. Klabbers (Международная аналитика, 2022)
Jan Klabbers is a Dutch Professor at the University of Helsinki. He is a Member of the Finnish Academy of Sciences and Letters, a member of the editorial board of the European Journal of International Law. Klabbers is the author of The Concept of Treaty in International Law (1996), An Introduction to International Institutional Law (2002, 3rd edition 2015), co-editor of Towards Responsible Global Governance (2018). Professor Klabbers has also published around 200 book chapters and articles (in the European Journal of International Law, International Organizations Law Review etc.) He is famous for delivering lectures during visiting positions at NYU Law School (2009-10), the Graduate Institute for International and Development Studies (2008, 2013, 2015), and the University of Paris-II and Paris-I (2011, 2017).